HISTORY OF ESTABLISHMENT AND DEVELOPMENT OF MUHAMMADIYAH KENDARI HIGH SCHOOL IN SOUTHEAST SULAWESI - Muallimah, Muallimah (Jurnal Multidisipliner Bharasumba, 2023)
The purpose of this study is to find out the History of the Establishment and Development of SMA Muhammadiyah Kendari in Southeast Sulawesi. The type of research used in this study is descriptive qualitative with a historical approach. Data collection techniques used include: heuristics, source criticism, interpretation and historiography. Data analysis techniques used are deduction, induction, comparative. The results of this study reveal that Muhammadiyah Kendari High School was established in 1968 and has gone through 7 leadership changes starting in 1968-2020. The first leader, Mr. Drs. H. Anwar Period 1968-1970 and led by the two fathers Mahmud Injjil Period 1970- In 1974, during their leadership, Muhammadiyah Kendari High School was still located in the old city and used 1 building. Then in the third leadership of Mr. H. Ahmad Aljufri for the period 1970-1974 Muhammadiyah High School during his leadership he made many changes in terms of development, in terms of the learning process, and administration at this time was quite successful. Then the following year was attended by Mr. Arqam Ali, he only had to continue the program that had been implemented before. From a physical standpoint and the learning process still applies the method from the previous leadership. After that, the head of the school was detained by Mr. Rahman BA. During his leadership period, the building which had previously started to break down was finally repaired and made into a computer lab. Besides that, the learning and administrative processes that were managed by him were very good. Mr. Ismail was the VI principal of the school. During his leadership, he was not much different from the previous leadership, who still imitated the leadership model of Mr. Ahmad Aljufri. During his leadership, he also built a building for the library. He put more emphasis on improving the learning process so that the vision and mission of SMA Muhammadiyah can be achieved. And finally, the leadership of Mr. H. G. Taslim, during his leadership period, experienced a decline in terms of human resources, in this case students from year to year due to the large number of public and private schools that were opened so that SMA Muhammadiyah Kendari became less interested. However, the facilities provided are adequate so that Muhammadiyah Kendari High School is currently accredited A.